(untitled) (Journal of Partial Differential Equations, 2015)
The Cauchy problemfor the wave equation with bi-inverse square potential on Euclidean plane is solved in terms of the two variables Appell F2 hypergeometric functions. Our principal tools are the Hankel transforms and the special functions of mathematical physics.